Applications of 18(F) FDG PET/CT in oncology - Ahmad Saad, Fathinul Fikri; Nordin, Abdul Jalil; Cheah, Yoke Kqueen; Ahmad Saad, F. N. (Universiti Putra Malaysia Press, 2015)
The escalating costs of conventional diagnostic technology in oncology have yet to obviate futile surgery intervention and the spiralling treatment cost. The evolution in engineering technology which looks at the correlation of the anatomy and the function of tumours i.e. Positron Emission Tomography-Computed Tomography (PET-CT) have impacted on the improved diagnostic accuracy and treatment in oncology. Clinical data have demonstrated that the information provided by PET/CT often changes patient management. This review addresses the value of PET-CT as a surrogate molecular marker in tumours and to discuss some issues in adopting PET/CT in routine daily practice as supported by the numbers of literature reviews of its application in oncology since it was first commercialized in 2001. The description of the technology used in multimodality imaging has gained encouraging interest among physicians, policy makers and insurance companies on the importance of the PET-CT, for which roles are not limited to the staging, disease prognostication and treatment monitoring with potential impact on treatment cost and justification of radiation safety for the patient. PET/CT is a useful tool in cancer investigation as evidenced by its role as a surrogate marker in underpinning the cellular reprogramming of different pathological entities.